2021
DOI: 10.1371/journal.pone.0245287
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 blockade and interferon-α induce proinflammatory transcriptional changes in the tumor immune landscape that correlate with pathologic response in melanoma

Abstract: Patients with locally/regionally advanced melanoma were treated with neoadjuvant combination immunotherapy with high-dose interferon α-2b (HDI) and ipilimumab in a phase I clinical trial. Tumor specimens were obtained prior to the initiation of neoadjuvant therapy, at the time of surgery and progression if available. In this study, gene expression profiles of tumor specimens (N = 27) were investigated using the NanoString nCounter® platform to evaluate associations with clinical outcomes (pathologic response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…[22] In acute myeloid leukemia and melanoma, patients with higher COL1A2 expression had longer overall survival. [23] In our study, COL1A2 was also down-regulated in radiation-resistant exosomes and was associated with a favorable prognosis in NPC patients, which is in line with the previous evidence that COL1A2 was good prognostic factor. These findings show the promising potential of exosomes as a novel biomarker for the evaluation of NPC radioresistance.…”
Section: Proteomic and Bioinformatic Analysis Revealed Altered Cargos...supporting
confidence: 92%
“…[22] In acute myeloid leukemia and melanoma, patients with higher COL1A2 expression had longer overall survival. [23] In our study, COL1A2 was also down-regulated in radiation-resistant exosomes and was associated with a favorable prognosis in NPC patients, which is in line with the previous evidence that COL1A2 was good prognostic factor. These findings show the promising potential of exosomes as a novel biomarker for the evaluation of NPC radioresistance.…”
Section: Proteomic and Bioinformatic Analysis Revealed Altered Cargos...supporting
confidence: 92%
“…The other genes including FGFR4, GNAI1, CD36 and FLT1 could alter the tumor microenvironment and further impact ICIs' clinical e cacy, combination their inhibitors and ICIs might be better for melanoma [30][31][32][33]. Khunger et al [34] found that COL1A2 was associated with cancer development and progression, and patients with melanoma were more likely to be bene t from anti-CTLA-4 inhibitors when COL1A2 was highly expressed. Moreover, for the Notch signaling pathway, Cho et al [35]found that it could affect activation of cytotoxic T cells, in ammatory immune microenvironment, in ammatory expression pro le and immunogenicity, and Li et al [36] reported that patients with nonsmall cell lung cancer (NSCLC) treated by ICIs could own longer survival time if they had high-mutated Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that several of the SHREK proteins, such as PSGL-1 [ 5 ], CD43 [ 37 ], CD164 [ 34 , 38 ], TMEM123 [ 39 ], MUC1 [ 40 ], and MUC4 [ 41 ], are induced by interferons. However, SHREK proteins in general are likely different from interferon-induced restriction factors, and can be constitutively expressed in specific cell populations.…”
Section: Discussionmentioning
confidence: 99%